MANAJEMEN PBRUBAHAN PADA DIRBKTORAT JENDRAL PERBENDAHARAAN (DJPBN) - , Maya Pahlevi Mahardika ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Changes often occur in organizations which have an advantage / profit oriented . But change can also occur in non - profit-oriented companies as happened in the Directorate General of Treasury ( DJPBN ) . One of the Echelon I in the Ministry of Finance is implementing reforms since 2004 in response to public demand the management of the state budget that is transparent, accountable , integrated and performance-based . State Treasury and Budget System ( SPAN ) as an information technology -based systems intended to support the achievement of the principles of managing the budget . Attempts are often made changes in many organizations and many have failed . Change Readiness Survey in order to implement SPAN conducted in November 2010 to January 2011 shows that the perception of employees on average are in 3.58 of a scale of 5 ( 1 = positive , 5 = negative ) . This suggests that the level of perception and readiness of employees to implement SPAN still requires significant improvement . To that end , the purpose of this study is : 1 ) to identify and evaluate management changes made by DJPBN and 2 ) to identify problems that occur in the management of changes made DJPBN . To achieve the research objectives , the instruments used in this study guide includes in-depth interviews ( in-depth interview ) to gather information from key informant who is an official in the Directorate of Treasury and Ambassador SPAN Transformation Coordinator . Research results show that the analysis is based on DICE Framework , Project SPAN has a fairly high likelihood of success because it is in the Win Zone . But the effort factor requires the most attention because of the effort required of employees is large enough that 20 % to 40 % . Based on the analysis of Ulrich Initiative and Process Change Model , the key success factors that have less value is the vision shaping / forming vision and creating need / creates needs . While based Ulrich Culture Change Models , gaps appear in the Workflow , Communications or Information Flow , Flow Decision or Authority , Human Resources and Flow